2009
DOI: 10.1590/s1519-69842009000100020
|View full text |Cite
|
Sign up to set email alerts
|

Development and reproductive performance of Swiss mice in an enriched environment

Abstract: The present study investigated the effects of environment enrichment on the development and reproductive performance of an outbred Swiss strain. Physical enrichment consisted of free access of animals to tubular devices of different shapes and sizes. The development evaluation was done by monitoring growth rate during 39 days, from weaning (21 days) to the onset of sexual maturity (60 days of age). Over five consecutive gestations (105 days), the following variables were monitored: litter size, number of anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Enrichment enhances male mating success in laboratory-reared flies [74] , [75] ; prolongs reproductive lifespan in domestic hens [76] ; and in mammals, enrichment seems to increase the number of infants succesfully weaned by females in laboratory mice [77] (though cf. [78] ) and farmed mink [79] . However, no study has investigated the effects of enrichment in both sexes, through all stages of reproduction from mating inspections to weaning; nor has any study identified the mechanisms underlying any observed success.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment enhances male mating success in laboratory-reared flies [74] , [75] ; prolongs reproductive lifespan in domestic hens [76] ; and in mammals, enrichment seems to increase the number of infants succesfully weaned by females in laboratory mice [77] (though cf. [78] ) and farmed mink [79] . However, no study has investigated the effects of enrichment in both sexes, through all stages of reproduction from mating inspections to weaning; nor has any study identified the mechanisms underlying any observed success.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been found that EE promotes a greater number of viable oocytes induced by superovulation in rats [ 16 ]. On the other hand, other authors did not find any effect of EE on reproductive parameters [ 17 , 18 ]. Despite these findings, further information is required on the effect of EE on reproduction in mice breeding colonies and their progeny.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies in mice reported controversial findings on the effect of EE on reproductive performance. Some authors suggest that EE does not affect the reproductive outcomes of Swiss Webster and C57BL/6J mice using physical enrichment, such as plastic devices of different shapes and sizes, or cotton squares [ 17 , 18 ]. On the other hand, other authors reported that physical EE items and the period of exposure resulted in larger body weights of the F1 or F2 offspring generations, addressing a relevant phenotype effect [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…En última instancia, se trataría de "enriquecer el ambiente para potenciar al cerebro" (Sale, Berardi, y Maffei, 2009). Esta complejidad proporciona también estimulación a nivel visual, somatosensorial e incluso olfatorio (Carvalho, Araujo, Farias, Rocha-Bezerra, y Cavalheiro, 2009;Nithianantharajah y Hannan, 2006;Redolat y Mesa-Gresa, 2011). El periodo durante el cual se mantienen los animales en estas condiciones y la edad de los mismos varía en función de los objetivos del estudio, de los análisis y pruebas que se realicen y de las hipótesis que guíen la investigación.…”
Section: Resumen Abstractunclassified